Reconstruction of Equality Before the Law: An Islamic Legal Perspective in the Context of Social Inequality - Ahmad Alimuddin (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This paper explores the integration of Islamic legal principles, specifically justice (adl) and equality (musawah), to address social inequalities in Indonesia’s diverse, post-pandemic society. The objective is to develop an inclusive legal framework aligned with national values. Employing an interdisciplinary approach combining Islamic law, sociology, and economics, the study analyzes theological and juridical foundations from the Qur’an and Hadith, alongside empirical data. Results show progress in reducing social disparities, with the Gini index dropping to 0.375 by March 2025 and poverty rates declining to 8.47 percent. Instruments like productive zakat, digital waqf, and sharia microfinance, supported by digital platforms such as e-court Syariah, have enhanced wealth redistribution and access to justice for marginalized groups. The main novelty lies in proposing an egalitarian family law reform through the Musawah Framework and contextual ijtihad to restore Islam’s original egalitarian values. Despite challenges like conservative resistance and digital divides, these reforms promise sustainable solutions for inclusive development, reducing socio-economic disparities, and strengthening Indonesia’s legal system. [Tulisan ini mengkaji integrasi prinsip hukum Islam, khususnya keadilan (adl) dan kesetaraan (musawah), untuk mengatasi ketidaksetaraan sosial di masyarakat Indonesia yang beragam pasca-pandemi. Tujuannya adalah membangun kerangka hukum inklusif yang selaras dengan nilai-nilai nasional. Dengan pendekatan interdisipliner yang menggabungkan hukum Islam, sosiologi, dan ekonomi, penelitian ini menganalisis landasan teologis dan yuridis dari Al-Qur’an dan Hadis serta data empiris. Hasilnya menunjukkan kemajuan dalam mengurangi disparitas sosial, dengan indeks Gini turun menjadi 0.375 pada Maret 2025 dan tingkat kemiskinan menurun menjadi 8,47 persen. Instrumen seperti zakat produktif, wakaf digital, dan keuangan mikro syariah, didukung platform digital seperti e-court Syariah, telah meningkatkan redistribusi kekayaan dan akses keadilan bagi kelompok marginal. Kebaruan utama terletak pada usulan reformasi hukum keluarga egaliter melalui Musawah Framework dan ijtihad kontekstual untuk memulihkan nilai kesetaraan asli Islam. Meskipun menghadapi tantangan seperti resistensi konservatif dan kesenjangan digital, reformasi ini menjanjikan solusi berkelanjutan untuk pembangunan inklusif, pengurangan disparitas sosial-ekonomi, dan penguatan sistem hukum di Indonesia.]